The impact CSR Disclosure on Earnings Quality: Analytical Study on Saudi Basic Materials Sector - Al-Maliki, Sarah Abdullah Ahmed; Abdul Rahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
The current study aims to gain insight on the effect of social responsibility disclosure on the quality of earnings in (42) Saudi Basic Materials companies listed in the Saudi Financial Market. The extrapolation approach has been used to achieve the goals of the study. Also, the descriptive analytical approach has been employed to analyze the content of the financial reports of the sample companies for the period (2015 – 2017) in order to determine the level of disclosure of social responsibility. The quality of earnings has been measured by using the Modified Jones Model. The most significant study findings show that 92.5% of the sample companies disclosed their social responsibility using descriptive disclosure methods. The study findings also show that there is a statistically significant relationship between disclosure of social responsibility and between the improvement of the quality of earnings in the Basic Materials sector due to the strong positive correlation between discretionary accounting accruals and disclosure of social responsibility. The study has also found that there is a statistically significant relationship between social responsibility and between the effectiveness of the accruals method in measuring the quality of earnings in the Saudi Basic Materials sector, where the accruals quality method proved to be efficient in measuring the quality of earnings. In view of the findings, the study recommends to actively promote the role of the organizations that regulate social responsibility in order to increase the level of social responsibility, and to promote the role of monitoring which will in turn improve the quality and level of earnings.